Access to Finance and Sustainable Human Development: Does Institutional Quality Matters in Developing Countries? - Kamalu, Kabiru; Ibrahim, Wan Hakimah Binti Wan (International Journal of Membrane Science and Technology, 2023)
Access to finance plays an important role in boosting economic activities, human capital development and access to health care, which promote human well-being. this study examines the heterogenous relationship between access to finance and sustainable human development in 21 developing countries, from 1996 to 2020. The study uses group-mean FMOLS and DOLS estimators with deterministic trend. The results show that the three proxies of access to finance promote sustainable human development in developing countries, but the effect of number of ATMs per 100,000 people is higher than that of number of commercial bank branches and domestic credit to private sector. The results also show that institutional quality matters as it enhances the positive effect of access to finance on sustainable human development for all the three proxies of access to finance. Government spending, Institutional quality and FDI found to promote sustainable human development in the long run. To promote sustainable human development, policymakers should pursue policies, programs and incentives that motivate commercial banks to establishes more branches and ATMs not only in urban centres but also in villages and remote locations.